The effect of body shape and swimsuit type on the comfort of Chinese women wearing swimsuits. Issue 7 (April 2023) - Jiang, Ao; Yao, Xiang; Cheung, Vien; Taylor, Lindsey Waterton; Tang, Haowen; Fang, Zhixiong
Among the fitness and body shaping exercises of Chinese women, swimming has become an increasingly popular sporting activity. Swimsuits are fundamental to participation in this sport and paramount to achieving the wearers' aim of participation. A survey of 3348 Chinese women showed that body fit is central to the purchase of a swimsuit, whether one piece or two piece, with the two-piece swimsuit proving the most popular in terms of comfort. This survey revealed that the comfort of a swimsuit is relative to the design variables of the swimsuit style, the material/body cover factor and, informed by the female form, body size and body shape. This is particularly pertinent in both the right and left anterior mammary regions and also the left lateral mammary region for the female wearer to stay comfortable during swimming when she moves in the water. This study investigated the factors that affect the comfort of women wearing swimsuits when they swim. The two-piece swimsuit was considered the most comfortable. It was also found that swimsuits negatively affect women's chest area. These results present important considerations for swimsuit manufacturers.